Akhlak Sebagai Fondasi Pendidikan Dalam Perspektif Ustadz Abdul Somad dan Buya Yahya : Pemahaman Tentang Akidah Akhlak - Alihan Satra; Dwi Adelia; Reza Anjani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Morals and education are two important aspects in the formation of an individual's character or personality. In the Islamic view, this morality is considered a very strong foundation of education. Two prominent scholars in Indonesia who are famous for their tausiyah that we often hear and meet, both on television and social media, one of them is YouTube. Where he has the same view about the importance of morality in education. The purpose of this study is to analyze the views of Ustadz Abdul Somad and Buya Yahya regarding morality as the foundation of education. The research method used in this study is a literature review, namely by using YouTube as a data source as well as books and articles related to morals and education. The results of this study show that the views between Ustadz Abdul Somad and Buya Yahya are the same about the importance of morality in education. They argue that morals are a strong foundation of education and must be taught from an early age. They also emphasized the importance of moral education in the formation of a good individual personality.